An experimental study on the effects of various mix proportions and constituents on the mechanical and durability properties of low-carbon UHPC - Maskey, Progress Man; Pennung Warnitchai; Thanakorn Pheeraphan; Raktipong Sahamitmongkol; Krishna, Chaitanya; AIT Scholarship (Pathum Thani, Thailand : Asian Institute of Technology, 2025)
In December 2021, Thai Cement Manufacture Association (TCMA) in collaboration with Thailand Concrete Association (TCA) developed 2Thailand 2050 Net Zero Cement & Concrete Roadmap3 which drives Thai cement and concrete industry toward Net Zero GHG emission by 2050. In support of this roadmap, this study investigates the use of the Modified Andreasen and Andersen (MAA) particle packing model to develop low-carbon ultra-high-performance concrete (UHPC) utilizing industrial-grade supplementary cementitious materials (SCMs) with reduced carbon footprints that are locally available in Kingdom of Thailand. The study examines the effectiveness of 2SCG Hybrid Cement3 and SCMs like limestone powder, quartz powder and silica fumes in creating a high density and low porosity UHPC which is unexplored in current literature.A Design of Experiment (DOE) approach is used to create a UHPC mix design. Experimental results confirm that MMA is highly effective in developing UHPC mix designs capable of achieving high compressive strength, with compressive strength reaching up to 146.21 MPa. All DOE based UHPC exhibit superior flexural strength, exceeding 28.32 MPa, modulus of elasticity (MOE) varying from 42.00 GPa to 52.32 GPa and flowability exceeding 200 mm. Furthermore, the chloride ion Permeability, as measured by the Rapid Chloride Penetration Test (RCPT), showed a maximum charge passed of only 203 Coulombs, indicating excellent resistance to chloride ingress. The study also evaluates the embodied CO2 and Carbon Index (CI) of each UHPC mix design. Based on the experimental data, multi-level Response Surface Model (RSM) model is developed to optimize UHPC mix design for the application as a flexural strengthening material for the beam. The results demonstrate an improvement in the stiffness and ultimate load of the beam wrapped with optimized UHPC. These finding suggest that it is viable to produce UHPC with SCMs that are available in Thailand.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering in Structural Engineering
Thesis (M. Eng.) - Asian Institute of Technology, 2025
Keywords: High strength concrete; Concrete -- Environmental apsects